áp dụng tính chất \(\frac{a}{b}< 1\Rightarrow\frac{a+m}{b+m}< 1\left(m\in N\right)\)
Ta có: \(A=\frac{17^{18}-1}{17^{20}-1}< \frac{17^{18}-1-16}{17^{20}-1-16}\)\(=\frac{17^{18}-17}{17^{20}-17}=\frac{17.\left(17^{17}-1\right)}{17.\left(17^{19}-1\right)}\)\(=\frac{17^{17}-1}{17^{19}-1}\)
\(\Rightarrow A< B\)
\(A=\frac{17^{18}-1}{17^{20}-1}\Rightarrow17^2A=\frac{17^{18}-1}{17^{18}-\frac{1}{17^2}}=1-\frac{1-\frac{1}{17^2}}{17^{18}-\frac{1}{17^2}}\left(1\right)\)
\(B=\frac{17^{17}-1}{17^{19}-1}\Rightarrow17^2B=\frac{17^{17}-1}{17^{17}-\frac{1}{17^2}}=1-\frac{1-\frac{1}{17^2}}{17^{17}-\frac{1}{17^2}}\left(2\right)\)
\(\frac{1-\frac{1}{17^2}}{17^{18}-\frac{1}{17^2}}< \frac{1-\frac{1}{17^2}}{17^{17}-\frac{1}{17^2}}\Rightarrow1-\frac{1-\frac{1}{17^2}}{17^{18}-\frac{1}{17^2}}>1-\frac{1-\frac{1}{17^2}}{17^{17}-\frac{1}{17^2}}\left(3\right)\)
Từ \(\left(1\right);\left(2\right)\&\left(3\right)\Rightarrow17^2A>17^2B\Leftrightarrow A>B.\)
\(A=\frac{17^{18}-1}{17^{20}-1}\)
\(17^2A=\frac{17^2\left(17^{18}-1\right)}{17^{20}-1}=\frac{17^{20}-17^2}{17^{20}-1}=\frac{17^{20}-1-288}{17^{20}-1}=1-\frac{288}{17^{20}-1}\)
\(B=\frac{17^{17}-1}{17^{19}-1}\)
\(17^2B=\frac{17^2\left(17^{17}-1\right)}{17^{19}-1}=\frac{17^{19}-17^2}{17^{19}-1}=\frac{17^{19}-1-288}{17^{19}-1}=1-\frac{288}{17^{19}-1}\)
Ta có : \(\frac{288}{17^{20}-1}< \frac{288}{17^{19}-1}\)nên \(-\frac{288}{17^{20}-1}>-\frac{288}{17^{19}-1}\)
\(\Rightarrow A>B\)
* Xét : \(17^2A=\frac{17^2\left(17^{18}-1\right)}{17^{20}-1}=\frac{17^{20}-17^2}{17^{20}-1}=\frac{\left(17^{20}-1\right)+\left[\left(-17\right)^2+1\right]}{17^{20}-1}\)
\(=\frac{17^{20}-1}{17^{20}-1}+\frac{-17^{20}+1}{17^{20}-1}=1+\frac{-17^2+1}{17^{20}-1}=1+\frac{-288}{17^{20}-1}\)
* Tương tự xét \(17^2B=1+\frac{-288}{17^{19}-1}\)
Có : 1720 - 1 > 1719 - 1 => \(\frac{-288}{17^{20}-1}>\frac{-288}{17^{19}-1}\Rightarrow1+\frac{-288}{17^{20}-1}>1+\frac{-288}{17^{19}-1}\)
\(\hept{\begin{cases}17^2A>17^2B\\\text{mà}17^2>0\end{cases}}\Rightarrow A>B\)
Ta có:\(17^{18}-1< 17^{18}-1\)
=>\(\frac{17^{18}-1}{17^{20}-1}< \frac{17^{18}-1-16}{17^{20}-1-16}=\frac{17^{18}-17}{17^{20}-17}=\frac{17\left(17^{17}-1\right)}{17\left(17^{19}-1\right)}=\frac{17^{17}-1}{17^{19}-1}=B\)
=>A<B
Vậy A<B
chúc bạn học tốt !
nhớ k nha! thank!
=>
Ta có
\(\frac{a}{b}< 1=>\frac{a}{b}>\frac{a-n}{b-n}\)
\(\frac{17^{18}-1}{17^{20}-1}>\frac{17^{18}-17}{17^{20}-17}=\frac{17\left(17^{17}-1\right)}{17\left(17^{19}-1\right)}=B\)B
=>A>B
vậy ,........
hok tốt